A rare case of sarcoid myelitis complicating Löfgren's syndrome - Kristensen, Katrine; Møller, Janne; Terkelsen, Astrid Juhl; Harbo, Thomas; Gormsen, Lars Christian; Hansen, Ib Tønder; Bendstrup, Elisabeth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Neurosarcoidosis is a rare and serious condition. Rapid diagnosis and treatment are crucial to prevent morbidity and mortality. When neurological symptoms are not present at the time of diagnosis, CNS involvement can be undetected. We present a case of neurosarcoidosis complicating Löfgren’s syndrome and discus the challenges in diagnostics and treatment, that can be encountered.